A systematic literature review and meta‐analysis of community pharmacist‐led interventions to optimise the use of antibiotics. Issue 6 (28th February 2022) - Lambert, Maarten; Smit, Chloé C. H.; De Vos, Stijn; Benko, Ria; Llor, Carl; Paget, W. John; Briant, Kathryn; Pont, Lisa; Van Dijk, Liset; Taxis, Katja
Abstract : Aims: The aim of this systematic review is to assess the effects of community pharmacist‐led interventions to optimise the use of antibiotics and identify which interventions are most effective. Methods: This review was conducted according to the PRISMA guidelines (PROSPERO: CRD42020188552). PubMed, EMBASE and the Cochrane Central Register of Controlled Trials were searched for (randomised) controlled trials. Included interventions were required to target antibiotic use, be set in the community pharmacy context, and be pharmacist‐led. Primary outcomes were quality of antibiotic supply and adverse effects while secondary outcomes included patient‐reported outcomes. Risk of bias was assessed using the 'Cochrane suggested risk of bias criteria' and narrative synthesis of primary outcomes conducted. Results: Seventeen studies were included covering in total 3822 patients (mean age 45.6 years, 61.9% female). Most studies used educational interventions. Three studies reported on primary outcomes, 12 on secondary outcomes and two on both. Three studies reported improvements in quality of dispensing, interventions led to more intensive symptom assessment (up to 30% more advice given) and a reduction of over‐the‐counter supply up to 53%. Three studies led to higher consumer satisfaction, effects on adherence from nine studies were mixed (risk difference 0.04 [−0.02, 0.10]). All studies had unclear or high risks of bias across at least one domain, with large heterogeneity between studies. Conclusions: Our review suggests some positive results from pharmacist‐led interventions, but the interventions do not seem sufficiently effective as currently implemented. This review should be interpreted as exploratory research, as more high‐quality research is needed. Abstract :